Investigation of simple cubical space trusses as impact energy absorbers - Taha, Hussin Alghamdi; Abdulghaffar, Azhari Aljawi; Abdulmalik, Ali Alghamdi; Mehmet, Akyurt (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/